Pengaruh Iklan dan Brand Ambassador Idol Korea Terhadap Minat Beli Konsumen yang Dimediasi oleh Brand Image Pada Produk Samsung - Salsa Bela Fitri Anggita Susanti; Lukman Hakim (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to examine The Influence of Advertising and Korean Idol Brand Ambassadors on Consumer Purchase Intention Mediated by Brand Image in Samsung Products. A quantitative approach was employed using a simple random sampling technique involving teenagers in the Solo Raya region as respondents. Primary data were collected through an online questionnaire with a five-point Likert scale and analyzed using Structural Equation Modelling (SEM) via SmartPLS 3.0. The independent variables are advertising and brand ambassador, the mediating variable is brand image, and the dependent variable is purchase intention. The results indicate that advertising and Korean idol brand ambassadors have a positive and significant effect on consumer purchase intention, both directly and indirectly through brand image. Engaging and informative advertisements build a strong brand image, while the presence of Korean idols as brand ambassadors enhances emotional appeal, strengthening Samsung's brand image. Brand image plays a crucial mediating role, reinforcing the influence of advertising and brand ambassadors on consumers’ purchasing decisions.